(untitled) (CIPEEX, 2025)
Measles is an infectious disease caused by the Measles morbilivirus virus, and vaccination is the main form of prevention. Vaccination is a crucial strategy for preventing disease and has been designated one of the greatest public health achievements of the 20th century. With the success of the National Immunization Program (PNI) in preventing the transmission of measles, in 2016, Brazil received certification from the World Health Organization (WHO) for eliminating the circulation of the virus. However, due to a migration crisis in 2018 in the north of the country, it ended up losing this certification. This study aims to identify the prevalence of measles vaccination coverage in the Midwest in children up to 2 years of age and analyze the impact of the pandemic and anti-vaccine movements in the period before and after the pandemic. This is a retrospective quantitative study, in which the data used were collected from DATASUS, corresponding to the years 2018 to 2021. Since this platform is in the public domain, no submission to the Ethics and Research Committee was required. Thus, a reduction in measles vaccination rates was observed in the Midwest region, with an emphasis on the state of Mato Grosso do Sul, especially in the years 2020 to 2021, presenting a relationship with the COVID-19 pandemic and anti-vaccination movements. Therefore, there is a clear need for greater promotion of vaccination campaigns and strategies to prevent the spread of fake news that discourages such an essential practice as vaccination.